INCOME EFFECTS OF THE SOCIAL INSURANCE SYSTEM IN POLAND – EVALUATION - Podstawka, Marian (Acta Scientiarum Polonorum. Oeconomia, 2008)
The paper presents evaluation of income effects of the social insurance system in Poland. Social insurance system can realise so-called insurance solidarity for farmers and those employed in other sectors. However, this system can also be based on progression. The insurance solidarity has been examined in two aspects: macro- and micro-economic. The analysis shows that in macro-economic aspect, there is no solidarity of social insurance among insurance beneficiaries forming either the group of the employed in non-agricultural sectors or those running a farm. There is the solidarity among people employed in farming sector and running non-agricultural economic activity. However, in case of larger farms, the share of contributions in their income makes barely few per cent.